Pengaruh Tata Letak (Layout) Mesin Produksi terhadap Produktivitas Kerja Karyawan Pabrik Kerupuk Sehati 2 Citra Rasa Cibungkul Ciamis - Damayanti Wulandari; Rita Tri Yusnita; Suci Putri Lestari (CV. Ulil Albab Corp, 2023)
This study aims to determine the effect of the layout of the production machine on the work productivity of the employees of the Sehati 2 Rasa Cibungkul Ciamis Cracker Factory. The research method used is descriptive and verification method. The research population was the employees of the Sehati 2 Cracker Factory, Cibungkul Ciamis Flavor, with a total of 40 employees. The sample in this study amounted to 40 employees and used a saturated sample. Data collection was carried out through distributing questionnaires. The data analysis technique used is descriptive analysis and simple linear regression analysis. The results of this study indicate that there is no significant effect between the layout (layout) on work productivity at the Sehati 2 Rasa Cibungkul Ciamis Cracker Factory.